IMIDAZOLIUM BASED ETHER-NITRILE FUNCTIONALIZED IONIC LIQUIDS FOR CO2 REMOVAL FROM HYDROCARBONS - RAVICHANDAR, SHANTINI (2020)
Carbon dioxide (CO2) becomes abundant in the atmosphere due to the extensive burning of fossil fuels. The CO2 capturing technology is now being the main focus among researchers battling against the dramatic climate change. The limitation of current technology for example amine solvents is that, they are highly volatile. Ionic liquids (ILs) show distinctive characteristics as a potential for replacement of amine for CO2 capturing. The added characteristic of ILs is the ability to design the IL according to the specified task of application. The objective of this research is to synthesize and characterize low viscosity ionic liquids comprising of imidazolium-based ether-nitrile functionalized ionic liquids for CO2 capture, to investigate the effects of temperature and pressure on CO2 solubility in the ionic liquids and to regenerate and reuse the synthesized ionic liquid after CO2 capture.